Unemployment Modelled Through M|G|? Systems - Ferreira, M. A. M.; Filipe, J. A.; Coelho, M. (International Journal of Latest Trends in Finance and Economics Sciences, 2014)
Using the results on the M|G|? queue busy period, it is presented an application of this queue system in the unemployment periods parameters and distribution fubction study.